Analysis of Concentration of Heavy Metal (Pb) and Cadmium (Cd) In Waterfish (Eichhornia crassipes) in Indragiri River, Riau - Elya Febrita (International Journal of Ecophysiology, 2020)
Research has been conducted to determine the concentration of Lead (Pb) and Cadmium (Cd) heavy metals in water hyacinth (Eichhornia crassipes) in the Indragiri River Waters of Indragiri Hilir Regency in May-July 2016. Determination of the research station was carried out by purposive random sampling by considering environmental conditions based on community activities around the river and the existence of Eichhornia crassipes. The main parameters in this study include the concentration of heavy metals Pb and Cd in river water, sediments and Eichhornia crassipes, and physico-chemical parameters as supporting parameters. The results showed that the average concentration of Pb heavy metals in river water was 0.276 ppm and Cd was 0.126 ppm. The average concentration of heavy metals Pb in sediments was 4.61 ppm and Cd of 0.75 ppm. The accumulation of Pb and Cd Eichhornia crassipest heavy metals is included in the low category, namely the average concentration of Pb heavy metals in the root organ is 3.02 ppm, on the leaf stalk 2.61 ppm, and on the leaves 2.09 ppm. The concentration of heavy metal Cd at the root was 0.47 ppm, at the leaf stalk 0.39 ppm, and at the leaves 0.362 ppm